Low Gestational Age Is the Strongest Predictor for Severe Retinopathy of Prematurity and Adverse Outcomes at Two-Year Follow-Up in a Low Incidence Setting - Nobile, Stefano; Bordignon, Linda; Peretti, Anna Maria; Carnielli, Virgilio Paolo (Journal of Child Science, 2017)
We aimed to determine the risk factors for type 1 ROP and outcomes at 2 years of corrected age among preterms born < 30 weeks of gestational age (GA) in a low-incidence setting. A cohort study with 447 infants was conducted. Those who underwent laser therapy for type 1 ROP were compared with controls by univariate and multivariate analysis. Neurological development was assessed by Bayley scales. Using univariate analysis, gestational age, sepsis, necrotizing enterocolitis, and insulin administration were found to be associated with type 1 ROP. Only GA remained significant with logistic regression. Infants with type 1 ROP had worse visual and neurodevelopmental outcomes at 2 years. Predictors of impaired neurodevelopment were type 1 ROP, surfactant administration, and bronchopulmonary dysplasia. Low GA was found to be a strong predictor of type 1 ROP, which was associated (along with surfactant administration and bronchopulmonary dysplasia) with worse neurological development.
Keywords: preterm infant; retinopathy of prematurity; risk factors; gestational age; laser therapy